Structure‐reactivity relationships between the fluorescent chromophores and antioxidant activity of grain and sweet sorghum seeds. Issue 6 (16th February 2016) - Uchimiya, Minori; Ni, Xinzhi; Wang, Ming Li
Abstract: Polyphenolic structures are the putative cause of a variety of seed functions including bird/insect resistance and antioxidant activity. Structure‐reactivity relationships are necessary to understand the influence of polyphenolic chromophore structures on the tannin content and free radical quenching ability determined by the traditional calorimetric methods. This study investigated the relationships between the structural attributes of fluorescent chromophore and the following seed characterization methods: procyanidin (by acid‐butanol assay) and flavonoid (by vanillin assay) contents, radical quenching (by DPPH assay), electron‐donating capacity (by Fe III reduction), and λ max (by UV/visible spectrophotometry). Distinctively different response was observed for different seed categories: U.S. grain sorghum hybrids, African grain sorghum, and sweet sorghum. The U.S. grain sorghum varieties (low‐tannin to maximize the livestock digestion) responded only to the DPPH assay. For sweet sorghum and African grain sorghum, linear correlation was observed between (1) the antioxidant activity (2) the amounts of procyanidins and flavonoids, and (2) the aromaticity of fingerprint fluorescent structures. Abstract : Key chromophores of different grain pools.